E-WALLET SERVICE INNOVATION, SERVICE DELIVERY, AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY WITHIN SHOPEEPAY IN INDONESIA - Devona Valencia; Chrisanty Victoria Layman (Universitas Multimedia Nusantara, 2021)
Abstract- Indonesia's fast-growing digital payment industry is encouraging the emergence of new players. In a highly competitive industry and accompanied by COVID-19, e-wallet service providers compete to attract consumers and seller partners to use their services. This study aims to examine the effect of service innovation (SI), service delivery (SD), and customer satisfaction (CS) on customer loyalty (CL) of ShopeePay e-wallet users in Indonesia, especially during the COVID-19 outbreak. This study uses a quantitative method with non-probability sampling, namely judgment sampling, in which respondents are users of ShopeePay e-wallet service in Indonesia. Samples analyzed was 303 respondents with questionnaire data collection technique. The results shows that SI and SD mediated by CS, and CS itself has a positive and significant effect on CL of ShopeePay users in Indonesia. These findings indicate that ShopeePay Indonesia needs to develop SI and SD that meets customer needs and expectations to achieve CL. Keywords: Delivery; Indonesian e-wallet; Innovation; Loyalty; Satisfaction